Optimizing bladder volume to minimize OAR dose in cervical cancer HDR intracavitary brachytherapy: an experimental and analytical dosimetric investigation - Ariani, Tami Oktavia; Wirawan, Rahadi; Marzuki, Marzuki; Subroto, Rinarto; Makmur, I Wayan Ari; Qomariyah, Nurul (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to determine the optimal bladder volume that can balance the dose distribution to the organs-at-risk (OARs), specifically the bladder and rectum, and to analyze the relationship between variations in bladder volume and the dose received by these two organs during high-dose-rate (HDR) brachytherapy. Six bladder volume variations, namely empty, 100 cc, 150 cc, 200 cc, 250 cc, and 300 cc, were used to analyze the correlation between bladder volume and the radiation dose received by the bladder and rectum. An experimental approach was employed by observing the dose point distribution and the D2cc dose to both organs based on calculations from the Treatment Planning System (TPS), which were then compared with analytical calculations using a quadratic polynomial regression model via the Ordinary Least Squares (OLS) method. In general, the bladder point dose and D2cc dose increased with increasing bladder volume; however, the rectal dose demonstrated very high stability (90-100 cGy). Based on the variations in bladder volume, the optimal volume was 100 cc, as it protects the bladder by minimizing dose distribution and stabilizes the dose to the rectum. The statistical analysis results showed that the quadratic regression model had a high goodness-of-fit to the experimental data, with a coefficient of determination (R²) value of 0.92.